Federal Worker Protection Standard - Buffington, E. J., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet defines the Worker Protection Standard (WPS) and provides a summary of WPS requirements and exemptions.
CEPEP 10/01, updated 6/06.
This fact sheet was revised as part of the Comprehensive Worker Protection Standard Awareness Project for Colorado.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pesticides -- Safety measures; Pesticides industry -- Safety measures; Employees -- Protection; Agricultural laborers -- Safety measures; Pesticides -- Handling -- Safety measures